THE PLACE OF SPECIAL CLOTHES IN OCCUPATIONAL OCCUPATIONAL PROTECTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the role of special clothing in labor protection and the requirements for textile fabrics for the manufacture of special clothing.